Leaders’ meetings: facilitating or replacing the formal processes in the Western Balkan countries? - Vjollca Krasniqi, Nenad Markovikj, Ilina Mangova, Enriketa Papa-Pandelejmoni and Jovan Bliznakovski (H2020 project “Closing the Gap between formal and informal institutions in the Balkan”, 2018)
Leaders’s meetings not only represent a specific mechanism in the political arena, but they are alos a site where informality pervades formal politics shaping institutions and pushing actors to work through informal channels. To demonstrate how informality constitutes formal politics this through leaders’ meetings, we will first offer a definition of leaders‘ meetings followed up with a discussion of four case illustrations that have included the following: 1) the judicial reform in Albania in 2015-2016; 2)the EU coordination mechanism in Bosnia and Herzegovina in 2014-2015; 3) government formation following during the 2014 parliamentary elections in Kosovo, and 4) the Macedonian political crisis and Pržino process in 2014-2016. As we read this processes in detail we also offer a view on the effects of this informal practice in political decision-making.
Keywords: leaders' meetings, informality, EU, Macedonia, Kosovo, B&H, Albania